Teachers’ Day Speech by the President of India, Shri Pranab Mukherjee at the Presentation of National Award to Teachers - NCERT, (JOURNAL OF INDIAN EDUCATION, 2014)
I am delighted to be with you today on the occasion of the presentation of the National Awards on Teachers’ Day. I extend my heartiest congratulations to all the teachers who are receiving the Award for their commendable work and service to the nation. Today, the 5th of September, is the birth anniversary of the former President of India Dr. Sarvepalli  Radhakrishnan, a great philosopher, thinker, scholar and educationist of the country. Very many years ago, he had perceptively remarked and I quote, "Education should be imparted with a view to the type of society that we wish to build. We are working for a modern democracy built on the values of human dignity and equality.